2018
DOI: 10.3389/fncel.2018.00123
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Coding and Energy Efficiency Are Promoted by Balanced Excitatory and Inhibitory Synaptic Currents in Neuronal Network

Abstract: Selective pressure may drive neural systems to process as much information as possible with the lowest energy cost. Recent experiment evidence revealed that the ratio between synaptic excitation and inhibition (E/I) in local cortex is generally maintained at a certain value which may influence the efficiency of energy consumption and information transmission of neural networks. To understand this issue deeply, we constructed a typical recurrent Hodgkin-Huxley network model and studied the general principles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Thus, in Pyramidal/ChR2 mice, both somatosensory and optogenetic activation of pyramidal neurons induced proportional gamma activity and CMRO 2 responses, in line with previous studies showing that gamma oscillations modulate oxygenation of brain tissue. 10,11 In keeping with previous studies, we found that NMDAR blockade reduced gamma activity and CMRO 2 responses commensurably in these mice 46 and that AMPAR blockade disrupted the relationship between gamma activity and CMRO 2 , 1 greatly reducing gamma activity evoked by optogenetic stimulation of pyramidal neurons without affecting CMRO 2 . The dissociation between gamma activity and CMRO 2 was likely due to AMPAR blockade preventing recurrent feedback inhibition as this interaction between pyramidal neurons and PV interneurons is thought to be the basis of gamma oscillations.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, in Pyramidal/ChR2 mice, both somatosensory and optogenetic activation of pyramidal neurons induced proportional gamma activity and CMRO 2 responses, in line with previous studies showing that gamma oscillations modulate oxygenation of brain tissue. 10,11 In keeping with previous studies, we found that NMDAR blockade reduced gamma activity and CMRO 2 responses commensurably in these mice 46 and that AMPAR blockade disrupted the relationship between gamma activity and CMRO 2 , 1 greatly reducing gamma activity evoked by optogenetic stimulation of pyramidal neurons without affecting CMRO 2 . The dissociation between gamma activity and CMRO 2 was likely due to AMPAR blockade preventing recurrent feedback inhibition as this interaction between pyramidal neurons and PV interneurons is thought to be the basis of gamma oscillations.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, there is significant motivation for understanding the mechanisms by which neurons create or suppress connections to enable hierarchical parallel processing in the brain and explaining how learning, cognition and creative behavior emerge 3 – 8 . Moreover, the brain connections are thought to obey a constrained optimization, such as maximization of information processing capacity (efficiency) while minimizing the energy expenditure 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Most brain energy is used on electrical signaling, including action potential (AP) generation, maintaining resting potentials, dendritic integration, and synaptic transmission (Attwell and Laughlin, 2001; Harris et al, 2012; Howarth et al, 2012). The metabolic energy used for neural signaling constrains the flow of information within and between cells, which is dependent on neuron type (Sengupta et al, 2010), excitation/inhibition balance (Sengupta et al, 2013; Yu et al, 2018), coding strategy (Yang et al, 2017; Yu and Yu, 2017), and system size (Yu and Liu, 2014; Yu et al, 2016). Determining the signaling-related energy of different cell types has important implications for the brain’s evolution and function, which also offers considerable insights into the interpretation of functional imaging signals (Howarth et al, 2012; Magistretti and Allaman, 2015) and provides inspirations for engineers to mimic neural circuits to design neuromorphic devices (Cruz-Albrecht et al, 2012; Sengutpa and Stemmler, 2014).…”
Section: Introductionmentioning
confidence: 99%